Populism and De Facto Central Bank Independence. (July 2023) - Gavin, Michael; Manger, Mark
Although central bank independence is a core tenet of monetary policy-making, it remains politically contested: In many emerging markets, populist governments are in frequent public conflict with the central bank. At other times, the same governments profess to respect the monetary authority's independence. We model this conflict drawing on the crisis bargaining literature. Our model predicts that populist politicians will often bring a nominally independent central bank to heel without having to change its legal status. To provide evidence, we build a new data set of public pressure on central banks by classifying over 9000 analyst reports using machine learning. We find that populist politicians are more likely than non-populists to exert public pressure on the central bank, unless checked by financial markets, and also more likely to obtain interest rate concessions. Our findings underscore that de jure does not equal de facto central bank independence in the face of populist pressures.